Physicochemical and biometric characterization of the fruit Jiló (Solanum Gilo Raddi) (Research, Society and Development, 2022)
The eggplant (Solanum Gilo Raddi) has several benefits for human health and the study of its physical-chemical and biometric characterizations can help to improve its storage and commercialization conditions. Therefore, the objective was to study the physical-chemical characterization and the biometric characterization of the in natura jiló fruit acquired in the months of February, April and June 2021, in order to compare the results obtained. For the physicochemical characterization, the water content, pH, total soluble solids, fixed mineral residue and crude protein were evaluated. In the biometric characterization, the length, width, thickness and mass of the fruits were evaluated and, then, the means were compared using the Tukey test (p ≤ 0.05). The results showed the influence of the high water content present in the fruit in the other physicochemical analyzes and that the samples used in the different months of the year showed an elongated shape. It is possible to verify the importance of evaluating these characterizations, since they are of paramount importance for distribution centers and for the purchase of fruits by the final consumer.